2010
DOI: 10.1097/icl.0b013e3181d1d5a5
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Comfort During the Day Assessed by Instant Reporting in Different Types of Contact and Non–Contact Lens Wearers

Abstract: Hydrogel and silicone-hydrogel contact lens wearers' comfort scores are reduced at night compared with morning. The slight comfort reduction at night versus morning found in non-contact lens wearers might be related to ocular or general physical fatigue, which suggest the possibility that reduced end-of-day comfort reported by contact lens wearers might not be solely related to contact lens wear. The results of this study also suggest that interpretation of comfort scores should be carried out with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Reduced wearing time may be due to reduction in comfort after few hours of lens wear. 20 We found dryness in 63% of the subjects. Similar to our finding, Jones et al also found dryness in 50---65% of their CL wearers.…”
Section: Discussionmentioning
confidence: 97%
“…Reduced wearing time may be due to reduction in comfort after few hours of lens wear. 20 We found dryness in 63% of the subjects. Similar to our finding, Jones et al also found dryness in 50---65% of their CL wearers.…”
Section: Discussionmentioning
confidence: 97%
“…3,13 The magnitude of this reduction was such that at T 8 and beyond, comfort was significantly worse than at T 0 (p G 0.023). Comfort while wearing contact lenses was significantly inferior to the no-lens condition (stage A) at all times after T 6 (p G 0.003).…”
Section: -Hour Continuous Contact Lens Wear (Stage B)mentioning
confidence: 91%
“…1,2 The typical ocular discomfort and dryness sensations are low or absent immediately after insertion but increase in severity over the course of a day of wear. 3 Many subjects find these sensations at the end of the day to be unsatisfactory, and in some cases, it is intolerable, prompting lens removal before the desired wearing time. The dryness and discomfort response has been attributed to, or associated with, a series of potential causative factors including disturbance of the tear film, lens design, material characteristics, and interaction between the contact lens and its care system.…”
mentioning
confidence: 99%
“…Discomfort caused by contact lenses has been related to several factors such as dryness, protein adsorption, physiological factors and friction occurring during the blinking process, especially between the anterior side of the lens and the inner eyelid [3][4][5][6][7][8]. Clinical tests have been performed to understand and improve comfort, and have centered on the trial of different lens materials and ophthalmic solutions [9][10][11][12][13]. The dryness issue has been investigated by studies of the incorporation of wetting agents into contact lenses [8] and on the effect of water content of the lens [14].…”
Section: Introductionmentioning
confidence: 99%